Recyclable GO‐Arginine Hybrids for CO2 Fixation into Cyclic Carbonates. Issue 4 (28th November 2022) - Pintus, Angela; Mantovani, Sebastiano; Kovtun, Alessandro; Bertuzzi, Giulio; Melucci, Manuela; Bandini, Marco
Abstract: New covalently modified GO‐guanidine materials have been realized in a gram‐scale synthesis and purified by an innovative microfiltration. The use of these composites in the fixation of CO2 into cyclic carbonates is demonstrated. Mild operating conditions, high yields (up to 85 %), wide scope (15 examples) and recoverability/reusability (up to 5 cycles) of the material account for the efficiency of the protocol. Dedicated control experiments shed light on the activation modes exerted by GO‐l ‐arginine during the ring‐opening/closing synthetic sequence. Abstract : CO2 fix : A new covalently modified graphene−arginine oxide has been synthesized on a gram‐scale, spectroscopically characterized and effectively used for CO2 fixation and transformation into cyclic carbonates. Dedicated control experiments led to a full rationale of the reaction profile.